Effects of Manganese(II) Complexes of 2-[(1-Thienyl)Ethylidene]-Hydrazinecarbothioamide on Reproductive Function of Male Rats - Fahmi, N.; Bansal, Anil; Joshi, S.C.; Singh, R.V. (Asian Journal of Chemistry, 2010)
The animals treated with ligand 2-[(1-thienyl) ethylidene] hydrazinecarbothioamide (TSCZH) and its manganese(II) complexes [MnCl(TSCZ)H2O] and [Mn(TSCZ)2] resulted in a significant reduction in the weight of testes, and other sex accessories. They also bring about reduction in sperm motility and sperm density in testes and cauda epididymis. The sialic acid, protein and fructose contents of various reproductive organs were significantly lowered. The results of these findings have been presented and discussed.